2021
DOI: 10.1002/chem.202101168
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐Intercalative Platinum Anticancer Complexes Photoactivated by Visible Light

Abstract: Photoactivatable agents offer the prospect of highly selective cancer therapy with low side effects and novel mechanisms of action that can combat current drug resistance. 1,8-Naphthalimides with their extended π system can behave as light-harvesting groups, fluorescent probes and DNA intercalators. We conjugated N-(carboxymethyl)-1,8naphthalimide (gly-R-Nap) with an R substituent on the naphthyl group to photoactive diazido Pt IV complexes to form t,t,t-[Pt(py) 2 (N 3 ) 2 (OH)(gly-R-Nap)], R = H (1), 3-NO 2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Previous chemical characterization of Pt(IV) azido complexes/photoproducts and analysis of their behavior in the presence of biomolecules has shown that these prodrugs release reactive Pt(II) species and radicals upon photoreduction by light irradiation, which can interact with both proteins and DNA. 12,13,78,79 In the present study, we have used synchrotron techniques to provide new insights into the intracellular photoactivation of Pt(IV) azido complexes in single cancer cells. We analyzed the morphological changes in cells exposed to the coumarin complex Pt2 in the dark and upon light irradiation using cryo-SXT, and correlated them to the cellular distribution of platinum in both conditions in comparison with the dihydroxido complex Pt1 and the clinically established drug cisplatin using XRF.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Previous chemical characterization of Pt(IV) azido complexes/photoproducts and analysis of their behavior in the presence of biomolecules has shown that these prodrugs release reactive Pt(II) species and radicals upon photoreduction by light irradiation, which can interact with both proteins and DNA. 12,13,78,79 In the present study, we have used synchrotron techniques to provide new insights into the intracellular photoactivation of Pt(IV) azido complexes in single cancer cells. We analyzed the morphological changes in cells exposed to the coumarin complex Pt2 in the dark and upon light irradiation using cryo-SXT, and correlated them to the cellular distribution of platinum in both conditions in comparison with the dihydroxido complex Pt1 and the clinically established drug cisplatin using XRF.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In Figure 4 A, the absorption spectra of the three ligands are compared. L1 and L2 are characterized by a maximum absorption in the UV region, while L3, due to the “push–pull” effect, has a maximum in the blue region at 418 nm [ 17 ]. The absorption spectra of the three ruthenium complexes C1–C3 under the same conditions are compared in Figure 4 B.…”
Section: Resultsmentioning
confidence: 99%
“…The ligands L1, L2, and L3 alone were completely inactive, and this was probably due to their bulkiness with respect to the non-substituted naphthalimide. Planarity is important for strong intercalation, but all of these three ligands present potential steric hindrances, such as the presence of the pyridine linked to the imide moiety through the methylene fragment and the substituents on the aromatic rings [17]. Yet, all this notwithstanding, the naphthalimide ligands play a key role in the biological activity of A signal that is diagnostic for following the photolysis process is the methylene group singlet of the naphthalimide ligands (Figure S7), which shifts markedly when the naphthalimide is released via irradiation; therefore, this signal was used to study the kinetics of the photolysis (Table S1).…”
Section: Photocytotoxicity Towards Cancer Cellsmentioning
confidence: 99%
“…Following this finding that incorporating aromatic ligands could promote the cellular uptake of diazido Pt(IV) prodrugs, Sadler and co-workers attached the fluorescent 1,8-naphthalimide or its NO 2 and NMe 2 derivatives at the one of axial positions in complex 36 to produce complexes 92–94 ( Table 8 ) ( Shi et al, 2021 ). All the three complexes can undergo photo-decomposition upon 420 and 463 nm irradiation.…”
Section: Axial Ligandmentioning
confidence: 99%